Meet Felicity : an American girl - Tripp, Valerie, 1951-; Andreasen, Dan (Middleton, Wis. : Pleasant Co., 2000)
In Williamsburg in 1774, nine-year-old Felicity rescues a beautiful horse who is being beaten and starved by her cruel owner.
"Book one"--Cover.
"Ages 7 and up"--P. [4] of cover.
600
Accelerated Reader AR
Keywords: Horses -- Fiction; Williamsburg (Va.) -- Fiction